The royal letters of Baginda Omar : Sultan Terengganu Darul Iman IX Marhum Baginda (1806-1876) - Raimy Che-Ross; Yayasan Diraja Sultan Mizan (Kuala Terengganu : Yayasan DiRaja Sultan Mizan, 2017)
Sultan Terengganu Darul Iman IX, Marhum Baginda (1806-1876).
volume 2. The royal letters of Baginda Omar : Sultan Terengganu Darul Iman IX Marhum Baginda (1806-1876).
Includes bibliographical references (page 199-200) and index.
Keywords: Terengganu (Sultanate) -- History; Terengganu (Sultanate) -- Kings and rulers